A new approach to analyzing convergence and synchronicity in growth and business cycles: Cross recurrence plots and quantification analysis - Patrick M. Crowley; Aaron Schultz (Bank of Finland, 2010)
Convergence and synchronisation of business and growth cycles are important issues in the efficient formulation of euro area economic policies, and in particular European Central Bank (ECB) monetary policy. Although several studies in the economics literature address the issue of synchronicity of growth within the euro area, this is the first to address the issue using cross recurrence analysis. The main findings are that member state growth rates had largely converged before the introduction of the euro, but there is a wide degree of different synchronisation behaviours which appear to be non-linear in nature. Many of the euro area member states display what is termed here intermittency in synchronization, although this is not consistent across countries or members of the euro area. These differences in synchronization behaviors could introduce further challenges in managing the country-specific effects of the common monetary policy in the euro area.
URN:NBN:fi:bof-20140807487
Keywords: C65; E32; F15; 330; Euro area; business cycles; growth cycles; recurrence plots; nonstationarity; complex systems; surrogate analysis